Molecular detection of monkeypox and related viruses: challenges and opportunities - Ghate, Sudeep D.; Suravajhala, Prashanth; Patil, Prakash; Vangala, Rajani Kanth; Shetty, Praveenkumar; Rao, R. Shyama Prasad (Virus genes, 2023)
The recent widespread emergence of monkeypox (mpox), a rare and endemic zoonotic disease by monkeypox virus (MPXV), has made global headlines. While transmissibility ( R 0 ≈ 0.58) and fatality rate (0–3%) are low, as it causes prolonged morbidity, the World Health Organization has declared monkeypox as a public health emergency of international concern. Thus, effective containment and disease management require quick and efficient detection of MPXV. In this bioinformatic overview, we summarize the numerous molecular tests available for MPXV, and discuss the diversity of genes and primers used in the polymerase chain reaction-based detection. Over 90 primer/probe sets are used for the detection of poxviruses. While hemagglutinin and A-type inclusion protein are the most common target genes, tumor necrosis factor receptor and complement binding protein genes are frequently used for distinguishing Clade I and Clade II of MPXV. Problems and possibilities in the detection of MPXV have been discussed.